Mengukur Kepuasan dan Loyalitas Mahasiswa melalui Kualitas Pelayanan Administrasi Politeknik Negeri Jakarta - Sujiwo Priambodo; Hartoyo Hartoyo; Sylvia Rozz; Sujiwo Priambodo; Hartoyo Hartoyo (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2025)
This study aims to analyze the impact of service quality on student satisfaction and its subsequent effect on student loyalty at Politeknik Negeri Jakarta (PNJ). A survey method was employed, with a sample of 312 respondents selected using purposive sampling. The collected data were analyzed using Structural Equation Modeling (SEM) with LISREL software to assess the relationships between the variables. The findings reveal that service quality has a positive and significant impact on student satisfaction, which, in turn, significantly influences student loyalty. Specifically, the dimensions of service quality, such as tangible aspects, reliability, responsiveness, assurance, and empathy, were found to play critical roles in shaping students' perceptions of satisfaction and their subsequent loyalty to the institution. These results provide valuable insights for Politeknik Negeri Jakarta, suggesting that improvements in service quality can lead to enhanced student satisfaction and foster long-term student loyalty. Based on these findings, the study recommends that the institution focus on continuous improvement of its service quality, particularly in the areas identified as most influential, to build stronger relationships with students and improve overall institutional performance.